The Islamization of Traditional Arts: Transformation of Reyog Ponorogo in the Context of Javanese Cultural Identity - Saputro, Muhammad Handri Aris; Warto, Warto; Pitana, Titis Srimuda (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2025)
Islamization has been one of the dominant discourses in the Ponorogo region, shaping various aspects of social and cultural life. The traditional art of Reyog Ponorogo represents a local cultural practice that cannot be separated from this discourse. This study aims to examine the influence of Islamization discourse on the traditions of Reyog Ponorogo. The research employs a qualitative method with a descriptive approach and a critical paradigm. Data were collected through in-depth interviews, observation, and documentation, and analyzed using the interactive model developed by Miles and Huberman. Michel Foucault’s discourse theory (1926–1984) serves as the primary analytical framework. The findings reveal that Islamization discourse in Ponorogo has significantly transformed the values embedded in Reyog Ponorogo and shaped public perceptions of traditional culture. This transformation is evident in the modification of song lyrics, costume design, ritual offerings, and the gemblak tradition. Furthermore, Islamization has influenced how Reyog Ponorogo is practiced within the broader context of cultural development and preservation. The study contributes to a deeper understanding of shifting cultural identity in Ponorogo and demonstrates the relevance of Foucault’s theory in analyzing the dynamics of religious discourse. The originality of this research lies in its application of Foucault’s discourse theory to the transformation of Reyog Ponorogo, a perspective that has not been systematically explored in previous studies.